Homer & Langley a novel - Doctorow, E. L., 1931- (New York : Random House, 2009)
Homer and Langley Collyer are brothers, the one blind and deeply intuitive, the other damaged into madness, or perhaps greatness, by mustard gas in the Great War. They live as recluses in their once grand Fifth Avenue mansion, scavenging the city streets for things they think they can use, hoarding the daily newspapers as research for Langley's proposed dateless newspaper whose reportage will be as prophecy. Yet the epic events of the century play out in the lives of the two brothers, wars, political movements, technological advances and even though they want nothing more than to shut out the world, history seems to pass through their cluttered house in the persons of immigrants, prostitutes, society women, government agents, gangsters, jazz musicians . . . and their housebound lives are fraught with odyssean peril as they struggle to survive and create meaning for themselves.
Keywords: Collyer, Homer Lusk, -- 1881-1947 -- Fiction; Collyer, Langley, -- 1885-1947 -- Fiction; Brothers -- New York (State) -- New York -- Fiction; Recluses -- New York (State) -- New York -- Fiction; Eccentrics and eccentricities -- Fiction; Large type books; Biographical fiction